Mitigating Toxic Stress in At-Risk Youth through an Agriculture-Based After School Program (Global Journal of Human-Social Science, 2022)
Adverse childhood experiences and accompanying toxic stress have negative impacts on children Of particular interest then is identifying strategies that could help at-risk youth mitigate the impacts of toxic stress Using a phenomenology based qualitatively dominant research approach this study explores dynamics of toxic stress in at-risk youth and how the On The Rise program an agricultural-based after school program for at-risk youth addresses toxic stress
Keywords: agriculture based programs; at-risk youth; toxic stress; mitigating toxic stress